Menimbang Gadai Emas sebagai Instrumen Investasi Syariah - Hadi, Ahmad Chairul (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2012)
The increasing of gold prices and high interest of the community to invest in gold responded by Islamic banking through Islamic gold pawning services with the term